The potential value of quercetin for colorectal cancer: a systematic review and a meta-analysis of preclinical studies - Duan, Xiucheng; Zhang, Liyuan; Liu, Fenye (Frontiers in Pharmacology, 2025)
ObjectiveQuercetin, a ubiquitous natural flavonoid present in numerous medicinal plants and foods, has been widely recognized for its various bioactive properties. However, despite its potential, the preclinical animal studies evaluating its therapeutic efficacy in colorectal cancer (CRC) remain inadequate, and the existing clinical research in this area is still limited in quantity. These deficiencies hinder the practical application of quercetin in the treatment of colorectal cancer.MethodsOur comprehensive review involved systematically searching major databases—including PubMed, Web of Science, and Embase—up to April 2025 for relevant preclinical studies. The SYRCLE risk of bias tool was employed by researchers to evaluate each entry. Subsequently, data analysis was conducted using the statistical software Review Manager 5.4.ResultsThe results of our meta-analysis showed that quercetin treatment not only significantly reduced the incidence of CRC (SMD-1.22, 95% CI: −0.26 to −0.38, p = 0.004), but also alleviated inflammation and oxidative stress compared with the control group. Quercetin treatment effectively improved the degree of crypt lesions (SMD-1.40, 95%CI: −2.53 to −0.26, p = 0.02) and alleviated precancerous lesions in the animal model of CRC. In terms of tumor cell proliferation, quercetin had a significant inhibitory effect on cell proliferation during treatment, as determined by PCNA analysis (SMD -8.22, 95% CI: −10.48 to −5.95, p < 0.00001). Quercetin may promote apoptosis during treatment, but this hypothesis has not been supported.ConclusionOur study indicates that quercetin exerts beneficial effects across multiple facets of CRC treatment. Nonetheless, precise evaluation of quercetin’s impact on colorectal cancer demands further high-quality, large-scale animal and human studies to confirm our findings.Systematic Review Registrationhttps://inplasy.com, identifier INPLASY202550014.